Exfoliative cytology of body fluids: a study from provincial hospital of Jammu region, India - Gupta, Rajat; Dewan, Deepika; Raina, Rakesh; Gupta, Madhu (International Journal of Research in Medical Sciences, 2016)
Background: Cytological study of body fluids is an inexpensive and simple procedure useful in making diagnosis regarding etiology, understanding course of disease and to monitor the response to therapy. It has helped in staging and prognosis of the malignant tumours. The present study aims to understand cytology of various aspirated body fluids, categorize effusions into non neoplastic and neoplastic type with further classification of aspirated fluid as exudate and transudate. Methods: A total of 185 cases of aspirated fluids coming to Pathology Department of Government Hospital Gandhi Nagar for analysis were studied over a period of one year i.e. from Jan 2015 to Dec 2015.The fluid received was centrifuged and the remaining sediment was transferred with the help of pipette onto two glass slides and spread evenly. One was stained with Giemsa and other was stained with Papanicolaou stain. Leishman stain was done in suspicious cases of CSF. Improved Neubauer counting chamber was used for the cell counts. Results: Peritoneal fluid was most common aspirated fluid (49.7%) with overall male to female ratio was 1:1.6. Maximum cases belonged to age group of 30-40 years. Only (5.4%) 10 cases were neoplastic. Among malignant effusions maximum (60%) were adenocarcinoma, followed by squamous cell carcinoma (20%). Conclusions: Exfoliative fluid cytology is rapid and effective method for diagnosis, evaluation and it further guides us in clinical decision making regarding management of underlying pathology.